2021
DOI: 10.3390/buildings11110513
|View full text |Cite
|
Sign up to set email alerts
|

Learnings from User Digital Trail Post-Occupancy Evaluation before COVID-19 for Future Workplace Analysis and Design

Abstract: Data are required for optimizing workplace design, assessing user experience, and ensuring wellbeing. This research focuses on the benefits of incorporating post-occupancy evaluation (POE) data analysis by studying the digital trail of employees generated by the existing Wi-Fi infrastructure of the office. The objective is to enable a safe return to offices through compliance with COVID-19 space-capacity regulations and in consideration of the health and wellbeing of employees. Workplaces, teams, and people ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…When searching on Web of Science, Science Direct, and CNKI, it was found that the research results of POE evaluation methods in the fields of residential communities [24][25][26], schools [27][28][29], office buildings [30][31][32], urban parks [33,34], and urban leisure squares [35,36] have been significant. This theory can help us to understand the needs of users and improve the quality of project design and planning problems in planning and construction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…When searching on Web of Science, Science Direct, and CNKI, it was found that the research results of POE evaluation methods in the fields of residential communities [24][25][26], schools [27][28][29], office buildings [30][31][32], urban parks [33,34], and urban leisure squares [35,36] have been significant. This theory can help us to understand the needs of users and improve the quality of project design and planning problems in planning and construction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To understand how the workplace is developing, it is necessary to understand new work styles, patterns, and locations that will ensure organizations stay effective in the long term (Saurin et al, 2008). Current spaces have a level of digitalisation that enables to use data analytics from built-in infrastructure to collect data on spaces performance, use and users behaviour (Regodón et al, 2021).…”
mentioning
confidence: 99%